Agenda for educational reform in Latin America and the Caribbean - Puryear, Jeffrey M. (Inter-American Dialogue WashingtonUS, 1994)
Provides an overview of the growing debate on educational reform in Latin America and the Caribbean. Outlines the principle failing of the education sector in most countries of the region, stresses the need for fundamental, systematic reform and presents some policy options.